The Pathogenesis of the Demyelinating Form of Guillain-Barre Syndrome (GBS): Proteo-peptidomic and Immunological Profiling of Physiological Fluids - Ziganshin, Rustam H. (Mol Cell Proteomics, 2016)
Acute inflammatory demyelinating polyneuropathy (AIDP) - the main form of Guillain-Barre syndrome—is a rare and severe disorder of the peripheral nervous system with an unknown etiology. One of the hallmarks of the AIDP pathogenesis is a significantly elevated cerebrospinal fluid (CSF) protein level. In this paper CSF peptidome and proteome in AIDP were analyzed and compared with multiple sclerosis and control patients. A total protein concentration increase was shown to be because of even changes in all proteins rather than some specific response, supporting the hypothesis of protein leakage from blood through the blood-nerve barrier. The elevated CSF protein level in AIDP was complemented by activization of protein degradation and much higher peptidome diversity. Because of the studies of the acute motor axonal form, Guillain-Barre syndrome as a whole is thought to be associated with autoimmune response against neurospecific molecules. Thus, in AIDP, autoantibodies against cell adhesion proteins localized at Ranvier's nodes were suggested as possible targets in AIDP. Indeed, AIDP CSF peptidome analysis revealed cell adhesion proteins degradation, however no reliable dependence on the corresponding autoantibodies levels was found. Proteome analysis revealed overrepresentation of Gene Ontology groups related to responses to bacteria and virus infections, which were earlier suggested as possible AIDP triggers. Immunoglobulin blood serum analysis against most common neuronal viruses did not reveal any specific pathogen; however, AIDP patients were more immunopositive in average and often had polyinfections. Cytokine analysis of both AIDP CSF and blood did not show a systemic adaptive immune response or general inflammation, whereas innate immunity cytokines were up-regulated. To supplement the widely-accepted though still unproven autoimmunity-based AIDP mechanism we propose a hypothesis of the primary peripheral nervous system damaging initiated as an innate immunity-associated local inflammation following neurotropic viruses egress, whereas the autoantibody production might be an optional complementary secondary process.